Design and analysis of magnetorheological damping vibration isolation device for robotic grinding system - Yufei LIU; Chuanhao SHAO; Jinyong JU; Xi ZHANG; Lang WU (Journal of Advanced Mechanical Design, Systems, and Manufacturing)
It is significant to design a grinding device with vibration suppression function for robotic constant force grinding. In this paper, a novel magnetorheological damping vibration isolation device (MDVID) for robotic grinding system is proposed. Firstly, the MDVID is designed by integrating magnetorheological damping unit and connecting unit, and the whole prototype of the robotic grinding end effector is developed. Then, damping force output characteristics of the MDVID under different parameters are analyzed based on the mechanical model and Maxwell electromagnetic simulation software. On this basis, mechanical properties experiment of the MDVID is carried out to further reveal and verify damping force output regularity characteristics of the magnetorheological damping unit under different currents, compression speeds and compression displacements. Finally, based on the data of magnetorheological damping force, damping force model of the MDVID is established through data fitting, and experimental verification of different parameter conditions is carried out. The MDVID proposed in this paper effectively integrates magnetorheological damping smart materials and can be used for vibration suppression of the robotic grinding system.